Continuous fabrication of nanostructure arrays for flexible surface enhanced Raman scattering substrate - Zhang, Chengpeng (Sci Rep, 2017)
Surface-enhanced Raman spectroscopy (SERS) has been a powerful tool for applications including single molecule detection, analytical chemistry, electrochemistry, medical diagnostics and bio-sensing. Especially, flexible SERS substrates are highly desirable for daily-life applications, such as real-time and in situ Raman detection of chemical and biological targets, which can be used onto irregular surfaces. However, it is still a major challenge to fabricate the flexible SERS substrate on large-area substrates using a facile and cost-effective technique. The roll-to-roll ultraviolet nanoimprint lithography (R2R UV-NIL) technique provides a solution for the continuous fabrication of flexible SERS substrate due to its high-speed, large-area, high-resolution and high-throughput. In this paper, we presented a facile and cost-effective method to fabricate flexible SERS substrate including the fabrication of polymer nanostructure arrays and the metallization of the polymer nanostructure arrays. The polymer nanostructure arrays were obtained by using R2R UV-NIL technique and anodic aluminum oxide (AAO) mold. The functional SERS substrates were then obtained with Au sputtering on the surface of the polymer nanostructure arrays. The obtained SERS substrates exhibit excellent SERS and flexibility performance. This research can provide a beneficial direction for the continuous production of the flexible SERS substrates.